Injury talk: spontaneous parent–child conversations in the aftermath of a potentially traumatic event. Issue 4 (13th October 2017) - Alisic, Eva; Gunaratnam, Shaminka; Barrett, Anna; Conroy, Rowena; Jowett, Helen; Bressan, Silvia; Babl, Franz E; McClure, Roderick; Anderson, Vicki; Mehl, Matthias R
Abstract : Background: While talking about traumatic experiences is considered central to psychological recovery, little is known about how these conversations occur in daily life. Objective: We investigated spontaneous injury talk among parents and children in the aftermath of a child's hospitalisation due to physical trauma, and its relationship with children's socioemotional functioning. Methods: In a prospective naturalistic observation study, we audio-sampled the daily life of 71 families with the Electronically Activated Recorder after their child (3–16 years old) was discharged from hospital. We collected close to 20 000 snippets of audio information, which were double-coded for conversation characteristics, and measured children's socioemotional functioning with the Strengths and Difficulties Questionnaire (SDQ) at 6 weeks and 3 months postinjury. Findings: The children were involved in injury talk for, on average, 46 min/day, 9 min of which referred to emotions. Children had significantly more injury conversations with their mothers than with their fathers. The tone of injury conversations was significantly more positive than that of non-injury conversations. More direct injury talk was associated with fewer problems on the emotion subscale of the SDQ at 3 months. Other associations between aspects of injury talk and children's socioemotional functioning were mostly non-significant, although they appeared to be stronger at 3 months than at 6 weeks. Conclusions: Families spontaneously talked about the injury and associated issues for about the same amount of time per day as a therapist might within a session (a 'therapy hour'). Clinical implications: Making full use of naturally occurring injury talk may be a valuable direction for parent and family-focused postinjury interventions. However, the study design prevents causal inference, and further exploration is warranted.